Deficits of knowledge vs. executive control in semantic cognition: Insights from cued naming - Jefferies, Elizabeth (2007)
Deficits of semantic cognition in semantic dementia and in aphasia consequent on CVA (stroke) are qualitatively different. Patients with semantic dementia are characterised by progressive degradation of central semantic representations, whereas multimodal semantic deficits in stroke aphasia reflect impairment of executive processes that help to direct and control semantic activation in a task-appropriate fashion (Jefferies and Lambon Ralph, 2006). We explored interactions between these two aspects of semantic cognition by examining the effects of cumulative phonemic cueing on picture naming in case series of these two types of patient. The stroke aphasic patients with multimodal semantic deficits cued very readily and demonstrated near-perfect name retrieval when cumulative phonemic cues reached or exceeded the target name’s uniqueness point. Therefore, knowledge of the picture names was largely intact for the aphasic patients, but they were unable to retrieve this information without cues that helped to direct activation towards the target response. Equivalent phonemic cues engendered significant but much more limited benefit to the semantic dementia patients: their naming was still severely impaired even when most of the word had been provided. In contrast to the pattern in the stroke aphasia group, successful cueing was mainly confined to the more familiar un-named pictures. We propose that this limited cueing effect in semantic dementia follows from the fact that concepts deteriorate in a graded fashion (Rogers et al., 2004). For partially degraded items, the residual conceptual knowledge may be insufficient to drive speech production to completion but these items might reach threshold when they are bolstered by cues.